"Government Doesn't Have the Muscle": State, NGOs, Local Politics, and Disaster Risk Governance in Malawi. Issue 3 (1st July 2017) - Kita, Stern Mwakalimi
Abstract : The Sendai Framework for Disaster Risk Reduction, 2015–30, calls for countries to strengthen disaster risk governance systems as a pathway to disaster risk reduction. This paper assesses the disaster risk governance system in Malawi, Sub‐Saharan Africa, to understand how the positioning of multiple actors is contributing to the creation of an environment generating either positive or negative outcomes. The study utilizes a landscape governance analytical framework grounded within network governance theory and predominantly relies on qualitative approaches. The study finds that non‐governmental organizations are delivering the majority of disaster risk management services in the country. However, there are shortfalls within and across key actors and institutions that are frustrating progress and could reverse isolated gains that the country has made. While central government is largely detached from community‐level implementation, its incapacity is worsened by politicians and local government actors who have positioned themselves to capture risk reduction finance. The paper, therefore, questions the rationale behind the urgency in decentralizing disaster risk governance before addressing critical challenges within the local government system. These findings, while specifically for Malawi, are also pertinent to other developing countries struggling to deal with the consequences of climate variability and change.